An Anthology of Existence: Explorations into the Life and Works of Christopher Langford James (1952 - 2008) - Rontsch, Marc Anton (Stellenbosch : Stellenbosch University, 2017)
Thesis (DPhil)--Stellenbosch University, 2017.